Path as Spatial and Spiritual Category in A. Najjar’s Novel “The Exiles of the Caucasus” - I. A. Kazharova (Научный диалог)
The proposed study examines the value components that make up the figurative and semantic complex of a path in the novel by A. Najjar “The Exiles of the Caucasus.” In the context of conjugation of the spatial and spiritual hypostases of a path, the point of beginning and the end, the image of the guide, the intersection, the opposition “friend - foe” and associated with them motive of fate and overcoming are mainly singled out. The role of druidism in preserving the integrity of the space of the Adyghe ethnic group is outlined. On the example of separate episodes of the novel it is shown that the destruction of the native Circassian space is equivalent to its desacralization, and the latter makes the inevitable tragedy of the ethnic group. The proposed prototype of the guide, the Circassian Sheikh Mansur, is indicated. The vector of spiritual transformation occurring within the limits of another’s space is tracked and the symbolic implication of constant accentuation by the author of stability of external appearance is defined. It is proved that the result of the path depicted in the novel acquires any meaning only insofar as it is connected with its Beginning. Special attention is paid to the spiritual prerequisites laid down in the basis of A. Najjar’s creation of this novel, as well as the ability to “preserve the Motherland within himself” as one of the dominants of his worldview. The novelty of the study is that the path as a spatial and spiritual category in the novel “The Exiles of the Caucasus” by A. Najjar is explicated and analytically comprehended for the first time.